Driving Purchase Intention for Sustainable Intercity Bus Services through Social Media Marketing - Olfebri, Olfebri; Yuliantini, Yuliantini; Sitanggang, Rohana; Marina, Sandriana; Octaviani, Reni Dian (Indonesian Journal of Sustainability Accounting and Management, 2025)
This study examines the impact of social media marketing activities on consumer purchase intentions in the context of bus transportation services. Using a quantitative approach and SEM-PLS on data from a questionnaire to 272 respondents, results show that social media marketing activities have a significant and positive direct effect on purchase intentions. These activities not only enhance brand awareness but also positively influence brand associations in consumers’ minds. While brand awareness does not significantly affect purchase intentions, brand associations play a crucial role in positively influencing consumer decisions. Additionally, the study reveals that social media marketing does not indirectly influence purchase intentions through brand awareness but does significantly contribute to brand associations, which subsequently drive purchase intentions. These results emphasize the importance of leveraging social media as a strategic tool for building strong brand awareness and associations to ultimately increase consumer purchase intentions for bus transportation services.